2019
DOI: 10.1016/j.psychres.2018.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cognitive impairment and quality of life in euthymic bipolar patients

Abstract: During the euthymic state in bipolar disorder, cognitive functions often remain affected. Specifically, subjective and objective cognitive impairment might distinctly affect patients' quality of life (QoL); however, this question had not been examined previously in Japanese patients. Therefore, the current study investigated the associations between cognitive complaints, QoL, and objective cognitive functions. Forty patients in remission were recruited from the Hokkaido University Hospital, Sapporo, Japan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
1
16
1
1
Order By: Relevance
“…Recent research has suggested that cognitive complaints and depression severity affect social function, although objective cognitive impairments do not affect social function in major depressive disorder [34]. A relationship between cognitive complaints and social function has been reported in euthymic bipolar disorder [35]. There is an important correlation between social function and cognitive function, especially subjective cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested that cognitive complaints and depression severity affect social function, although objective cognitive impairments do not affect social function in major depressive disorder [34]. A relationship between cognitive complaints and social function has been reported in euthymic bipolar disorder [35]. There is an important correlation between social function and cognitive function, especially subjective cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Her ne kadar literatürde hasta yakınları ile kontroller arasında anlamlı fark saptamayan çalışmalar olsa da (6); BB olan hastalar ve yakınları arasında özellikle yanıt inhibisyonu ve planlama gibi yürütücü işlevler, sözel öğrenme, sözel bellek ve sözel çalışan bellek açısından benzerlik olduğu, bu işlev bozukluklarının BB için endofenotip adayı olabileceğini öne süren metaanaliz çalışmaları mevcuttur (7). Ayrıca güncel veriler mevcut bilişsel bozuklukların yaşam kalitesine olan olumsuz etkilerini de ortaya koymuş, konunun önemine tekrar vurgu yapmıştır (8,9). Bu nedenle bipolar bozuklukta bilişsel bozukluklar konusu güncelliğini korumaya devam edecektir ve bu alanda daha çok çalışmaya ihtiyaç olduğu görünmektedir.…”
Section: Introductionunclassified
“…21 Regarding the Japanese version of COBRA, it correlates with processing speed, 20 and quality of life in patients with euthymic bipolar disorder. 17 In Japan, COBRA is a useful tool to assess subjective cognitive function in the general adult population. Our objective was to investigate the mediator effect of subjective cognitive function in the relationship between affective temperaments, depressive symptoms, and functional disability.…”
Section: Neurocognitive Complaints Assessmentsmentioning
confidence: 99%
“…1 The correlation between depressive symptoms, subjective cognitive function, and functional disability are significant not only in patients with mood disorder but also in the general population. 1,17 However, the impact of affective temperaments on subjective cognitive function in the general adult population remains unknown. In addition, it is unknown if subjective cognitive function mediates the effect of affective temperaments on functional disability.…”
Section: Introductionmentioning
confidence: 99%